The Revised Statutes of Indiana: Containing, Also, the United States and Indiana Constitutions and an Appendix of Historical Documents. Vol. 1, at 366 (1881), Crimes, § 1957 - (:unkn) unknown (General Publisher, 1881)
Prohibited maliciously or mischievously shooting a gun, rifle, pistol, or other missile or weapon, or throwing a stone, stick, club, or other substance at a vehicle. Punishable by imprisonment for 30 days to 1 year and a fine of $10-100.
--
Keywords: DISCHARGE